2000
DOI: 10.1002/1097-0088(200009)20:11<1329::aid-joc537>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

A synoptic climatology of derecho producing mesoscale convective systems in the North-Central Plains

Abstract: Synoptic-scale environments favourable for producing derechos, or widespread convectively induced windstorms, in the North-Central Plains are examined with the goal of providing pattern-recognition/diagnosis techniques. Fifteen derechos were identified across the North-Central Plains region during 1986 -1995. The synoptic environment at the initiation, mid-point and decay of each derecho was then evaluated using surface, upper-air and National Center for Atmospheric Research (NCAR)/National Center for Environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…Bentley, Mote, and Byrd (2000) found that the presence of a weak thermal boundary, high convective instability, and a dry low-to-mid-tropospheric layer facilitates derecho formation in the north-central Great Plains. Similarly, Ashley, Mote, and Bentley (2007) showed that moisture, instability, and wind shear enabled by the large-scale setting are associated with derechos.…”
Section: Derechosmentioning
confidence: 99%
“…Bentley, Mote, and Byrd (2000) found that the presence of a weak thermal boundary, high convective instability, and a dry low-to-mid-tropospheric layer facilitates derecho formation in the north-central Great Plains. Similarly, Ashley, Mote, and Bentley (2007) showed that moisture, instability, and wind shear enabled by the large-scale setting are associated with derechos.…”
Section: Derechosmentioning
confidence: 99%
“…This synoptic set-up and event evolution, with the MCS of interest moving parallel to a zonal surface front, is similar toFig. 4inBentley et al (2000), associated with derechos.…”
supporting
confidence: 58%
“…Composite analysis of eight heat wave events by Bentley and Stallins (2008) illustrates that on these days, elevated surface dewpoint temperature anomalies . 38-58C are commonly associated with synoptic patterns and thermal profiles characterized by a strong capping inversion (e.g., 700-hPa air temperatures .…”
Section: Discussionmentioning
confidence: 99%
“…The sensible weather impacts from heat wave events and organized MCSs are both collectively influenced by enhanced low-level moisture (e.g., Kunkel et al 1996;Bentley et al 2000). Across the upper Midwest, the ; shaded according to scale), and wind vectors (reference at top right of panel) for the 99 warm-season EML days at MPX at 1200 UTC (e.g., day 10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation